The urban beautician : a practice of transferring ephemeral interventions in the public space via media into a work of art - Reinhuber, Elke (2020)
In this artistic research, I argue that a range of artistic practices is capable of addressing relevant issues in our material, specifically our urban, environment. In particular, conceptual interventions or non-theatrical performances, which are in most cases mundane everyday activities that require transformation through media to be understood as art. Yet, as human memory is susceptible, media is also required to provide proof of the action for archives or exhibitions, or simply as a memento of the artwork itself. Lens-based media, such as photography and video-recording, are in most cases the ideal form of documentation and distribution, while the actual performance is transferred to another genre of artistic practice and dissociated from the immediate experience of the moment.This paper introduces the enduring work of the author’s alter ego, The Urban Beautician, and defines her actions and documentation of this work within the framework of the conceptual and performance art scene. An assiduous assessment of her artistic ancestry is given and a catalogue of her endeavours, categorised by diverse subjects, arranged to isolate the themes and to connect the topics.